KYRGYZSTAN: POLITICAL HISTORY OF TWO DECADES OF INDEPENDENCE - PRYAKHIN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2011)
For over twenty years now the Soviet-successor states have been building new statehoods in the territory that used to be the Soviet Union; not all of them have been equally successful, but each has hastened to declare its devotion to democratic ideals and principles. During the first ten years of its independence Kyrgyzstan looked like a Central Asian “island of democracy”; since that time, however, the country has lived through two regime changes accompanied by the use of force, bloodshed, and mass disturbances. Below is a summary of the country’s political experience during the two decades of its independence.